Bipolar disorder and psychotropic medication: Impact on pregnancy and neonatal outcomes - Wisner, Katherine L. (J Affect Disord, 2018)
OBJECTIVE: The hypotheses were: (1) pregnant women with bipolar disorder (BD) have less favorable pregnancy outcomes than unaffected women, and (2) psychotropic treated women with BD have better outcomes than unmedicated women. METHOD: This prospective study included 174 mother-infant dyads. Women had BD without psychotropic exposure (BD-NP, n = 38), BD with psychotropic treatment (BD-P, n = 49), or neither psychotropic exposure nor major mood disorder (Comp, n = 87). Maternal characteristics were completed at 20 weeks gestation and evaluated for associations with delivery and birth outcomes. We performed multiple regressions on infant outcomes with adjustment for maternal age, race, employment status, use of illicit drugs and pre-pregnancy BMI. RESULTS: The BP-P, BP-NP and Comp groups varied significantly on sociodemographic characteristics. Women with BD were more likely to be less educated, unemployed, single, and use tobacco and illicit drugs than women in the Comp group. Compared to women with BD-NP, women with BD-P were more likely to be older and educated. Approximately 10% of all infants were delivered preterm. No significant differences in outcome occurred for APGAR scores < 8, NICU admissions, sex or infant length. Infants of mothers with BD-NP had significantly smaller head circumferences (HC) than the other groups, adjustment for confounding variables mitigated this association. CONCLUSIONS: The overall pregnancy outcomes for women with BD were similar to those in the Comp group. The reduced HC in women with untreated BD appears due to factors related to disadvantaged sociodemographic status, a higher proportion of female births, and/or a protective effect of medication in the BD-P group.